Large energy mode-locked phenomenon based on ZrS2 in Er-doped fiber laser. (January 2023) - Sui, Zhiqi; Yang, Fuhao; Han, Yun-ao; Fan, Weiyu; Li, Shuaimeng; Bai, Caixun; Lu, Cheng; Zhang, Wenfei; Wang, Guomei; Fu, Shenggui; Zhang, Huanian
Highlights: ZrS2 was prepared as a saturable absorber for generating passively mode-locked in an Er-doped fiber laser. The optical wavelength of 1531 nm was obtained by 1250 mW high-power pump, which made the saturated absorber have a high damage threshold. By changing the cavity length, the maximum monopulse energy obtained by mode-locked operation is 23.65 nJ. Abstract: With high nonlinear effect and low band gap value, ZrS2 is a promising material in photovoltaic application. In our work, a ZrS2 -polyvinyl alcohol thin film modulator was successfully prepared by liquid phase exfoliation. The modulation depth of ZrS2 saturable absorber is 6.3 % and its saturation intensity is 3.92 MW/cm 2 . Large energy mode-locked phenomenon was obtained in the Er-doped fiber laser with ZrS2 as an optical modulator. When the pump power was 1250 mW, the center wavelength, pulse repetition rate, and maximum pulse energy of the large energy mode-locked were 1531 nm, 604.23 kHz, and 23.65 nJ, respectively. This experiment proves that ZrS2 has excellent nonlinear absorption performance, also provides a reference for the future research of large energy mode-locked based on transition metal dihalogenateds.